ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENGEMBANGAN NAGARI SIAGA AKTIF DI KABUPATEN LIMA PULUH KOTA - Susana, Devi; Afrizal, Afrizal; Najmudin, Najmudin (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Village development is a program (or an effort)aimed to continuously improve the quality of life for the maximum welfare of the village people. Village development is multidimensional and multisectoral in nature. This development program is also seen or assessed from all fields including the health sector. With regard tothe quality of life in the health sector, the government has been conducting what is called the standby-active village (nagari) activities to boost the health of the rural community. But the findings of the Ministry of Health of the Republic of Indonesia show no nagari (or village) in the Lima Puluh Kota Regency managed to get into the independent village category since the launch of the standby and active village program. For this reason, it is important to look at the factors that influence the development of an active and standby nagari (village)to reach the level of independent village in the regency. This research uses a qualitative approach. This study selected three locations of active and standby villages (nagari) in the Lima Puluh Kota Regency, i.e. Nagari Pandam Gadang in the Gunung Mas District (Pratama Category), Nagari VII Koto Talago in Guguak District (Madya Category), and Nagari Batu Balang in Harau District (Purnama Category). Data collection was carried out through in-depth interviews with informants, as well as report documents and activities of the active standby nagari. Data analysis is carried out in stages through data reduction, data presentation, and drawing conclusions/verification. The research results shows a number of factors affecting the development efforts for the active standby nagari to become independent, namely the absence of active nagari forums, the lack of independent cadres, the lack of Community-Based Health Efforts (UKBM) apart from posyandu (integrated health post), low participation of the people, the business community and community organizations, and the low level of community participation fostering the Clean and Healthy Behavior (PHBS). This can be seen from the absence of community empowerment, resulting in low community participation and the lack of social change in the independent active-standby nagari program. So, a good evaluation and monitoring by the government and related parties of the active-standby nagari program is thus imperative. Key words: Nagari Siaga Aktif, Lima Puluh Kota Regency